A field comparison of different olive (Olea europaea L.) cultivars as host of the ash whitefly Siphoninus phillyreae (Haliday) - Pedemonte, María Laura; Bruno, Marina Anabel; Grilli, Mariano Pablo (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
The ash whitefly, Siphoninus phillyreae (Haliday) is an invasive polyphagous species that causes serious damage to their hosts, including olive (Olea europaea L.). Host use by S. phillyreae was observed in three olive cultivars (Arauco, Arbequina y Aloreña) in North of La Rioja province (Argentina) during 2007 and 2008. Eight leaves of six infested plants of each cultivar were sampled. Adults and inmature stages abundances of each leaf were recorded. These abundances per cultivar were compared using general linear mixed model. The results showed significant differences between the densities of adults and nymphs of S. phillyreae in each of the olive cultivars analyzed. Thus, our results indicate that this insect makes a different use of the olive cultivars, Arauco and Arbequina being the most used in the study area.